Microscopic mechanism for the 1/8 magnetization plateau in SrCu2(BO3)(2) - Nemec, M.; Foltin, G. R.; Schmidt, Kai Phillip (Physical Review B, 2012)
The frustrated quantum magnet SrCu2(BO3)(2) shows a remarkably rich phase diagram in an external magnetic field including a sequence of magnetization plateaux. The by far experimentally most studied and most prominent magnetization plateau is the 1/8 plateau. Theoretically, one expects that this material is well described by the Shastry-Sutherland model. But, recent microscopic calculations indicate that the 1/8 plateau is energetically not favored. Here, we report on a very simple microscopic mechanism which naturally leads to a 1/8 plateau for realistic values of the magnetic exchange constants. We show that the 1/8 plateau with a square unit cell benefits most compared to other plateau structures from quantum fluctuations which, to a large part, are induced by Dzyaloshinskii-Moriya interactions. Physically, such couplings result in kinetic terms in an effective hard-core-boson description leading to a renormalization of the energy of the different plateau structures which we treat in this work on the mean-field level. The stability of the resulting plateaux are discussed. Furthermore, our results indicate a series of stripe structures above 1/8 and a stable magnetization plateau at 1/6. Most qualitative aspects of our microscopic theory agree well with a recently formulated phenomenological theory for the experimental data of SrCu2(BO3)(2). Interestingly, our calculations point to a rather large ratio of the magnetic couplings in the Shastry-Sutherland model such that nonperturbative effects become essential for the understanding of the frustrated quantum magnet SrCu2(BO3)(2).